The Construction of Traditional Music in Madeira: A Brief Historical Tour - Santos, Filipe dos (2013)
This text aims to observe and analyze, from a historical perspective, the process of construction of traditional music – imbued in the global phenomenon of folklorization – in Madeira Archipelago, since the 19th century to the present time. Several aspects are considered: the conducting of folkloristic investigations (collection and analysis), with particular attention to musical traditions, inseparable from its authors; traditional musical instruments; the activity of musicians and musical groups; the folklore standardization carried out by official institutions.